Integrating service quality and Sharia governance in building customer loyalty in Islamic banking - Fielnanda, Refky; Nofriza, Eri (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study explores how service quality and Sharia governance directly influence customer loyalty in Islamic banking. It moves beyond procedural interpretations of Sharia compliance by examining how operational performance and institutional religiosity jointly shape long-term customer commitments.Methodology – An explanatory sequential mixed-method design was employed. In the quantitative phase, data were collected from 213 customers of the Bank Syariah Indonesia (BSI) in Jambi Province, Indonesia. The sample was selected using cluster random sampling, in which two of the three existing BSI branches were randomly chosen, and all customers from the selected branches participated as respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The qualitative phase followed an Interpretative Phenomenological Analysis (IPA) involving in-depth interviews with four long-term loyal customers to uncover the emotional, spiritual, and value-based dimensions underpinning their loyalty.Findings – Both service quality and Sharia governance significantly and directly affect customer loyalty, with Sharia governance exerting a stronger influence. The qualitative findings revealed four key loyalty-building patterns: spiritualized service experience, trust in Sharia supervisory structures, emotional connection with Islamic digital platforms, and personalized service grounded in ethics.Implications – For Islamic banks, fostering loyalty requires more than efficient service delivery and demands visible Sharia credibility and alignment with customers’ religious values and expectations.Originality – Departing from previous studies that examined operational or governance factors in isolation, this study integrates service quality and Sharia governance as parallel, mutually reinforcing drivers of customer loyalty. The developed loyalty framework captures the multidimensional interplay between faith, ethical congruence, and service experience in Muslim-majority banking context.